Analisis Kelayakan Buku Referensi Nonteks Sebagai Bahan Bacaan Populer Khasiat Gedebok Pisang Sebagai Alternatif Penurunan Kadar Gula Darah - Nirmalasari, Ridha; Nursalina, Nursalina; Septiana, Nurul; Hujjatusnaini, Noor (BIOEDUSCIENCE, 2024)
Background: The development of research results as a reading source is rarely used among the wider community, so documentation of information from research results is still very minimal. Therefore, it is necessary to develop products based on research results in the form of popular reading materials that are non-text, interesting, and practical, which can also be used as references to increase knowledge and information in the health sector. Methods: Design for developing a non-text reference book using the four-D model with four stages, namely define, design, develop, and disseminate. 2 expert validators first validate the feasibility of the product being developed before being disseminated. Products declared suitable for use as reading sources by validators are then disseminated to users who have met the criteria as respondents. Analysis of the level of product suitability was obtained from the assessment results of 25 respondents comprising 15 students and ten members of the general public. Product feasibility level data was analyzed quantitatively and descriptively. Results: The results of the product feasibility analysis based on small-scale tests obtained results with aspects of content feasibility (87.54%), presentation feasibility (84.60%), and usefulness (88.40%) so that an average of 86.85% or excellent qualifications was obtained. Good and declared worthy to be used as reference material and popular reading. Conclusions: The product of developing a non-text reference book about the benefits of banana gedebok is considered worthy with excellent qualifications and can be recommended as popular reading material among academics and the general public. Therefore, developing reference books based on research results is essential as an effort to document information in the health sector.